2010
DOI: 10.1159/000275672
|View full text |Cite
|
Sign up to set email alerts
|

Attention Network Functioning in Patients with Dementia with Lewy Bodies and Alzheimer’s Disease

Abstract: Background: Attention deficits are at the core of the defects in neuropsychological performance which define both dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD). Most studies have used separate tasks to test different attention abilities in patients with these diagnoses, precluding the assessment of any interaction among the different attention components. Methods: We used a version of the Attention Network Test in which the alerting, orienting and executive attention networks, along with their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
6
26
1
Order By: Relevance
“…In this study, we replicated previous findings regarding the functioning of attention networks and their interactions in people without cognitive impairment [11,12,13,14,15]. Our results showed that, in HC participants, the orienting network improved the subjects’ focusing of attention on the target location, fostering conflict resolution by incongruent distracters, a role attributed to the executive network.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, we replicated previous findings regarding the functioning of attention networks and their interactions in people without cognitive impairment [11,12,13,14,15]. Our results showed that, in HC participants, the orienting network improved the subjects’ focusing of attention on the target location, fostering conflict resolution by incongruent distracters, a role attributed to the executive network.…”
Section: Discussionsupporting
confidence: 89%
“…The results presented here provide information that is useful in the identification and understanding of preliminary stages of dementia. These results also suggest possible advances in therapeutic approaches to this disease that involve neuropsychological rehabilitation [14,39], pharmacological agents [23] or a possible combination of both methods.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations